2017
DOI: 10.33549/physiolres.933682
|View full text |Cite
|
Sign up to set email alerts
|

Preejection Period as a Sympathetic Activity Index: a Role of Confounding Factors

Abstract: In previous studies, one of the systolic time intervals – preejection period (PEP) – was used as an index of sympathetic activity reflecting the cardiac contractility. However, PEP could be also influenced by several other cardiovascular variables including preload, afterload and diastolic blood pressure (DBP). The aim of this study was to assess the behavior of the PEP together with other potentially confounding cardiovascular system characteristics in healthy humans during mental and orthostatic stress (head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…The preejection period or PEP is the time elapsed between the electrical depolarization of the left ventricle (Q in the QRS complex in the ECG) and the beginning of ventricular ejection and represents the period of left ventricular contraction with the cardiac valves closed (Lanfranchi et al, 2017); it is an index of cardiac sympathetic (β-adrenergic) activity (Krohová et al, 2017). The SI is purely based on the RR intervals.…”
Section: Discussionmentioning
confidence: 99%
“…The preejection period or PEP is the time elapsed between the electrical depolarization of the left ventricle (Q in the QRS complex in the ECG) and the beginning of ventricular ejection and represents the period of left ventricular contraction with the cardiac valves closed (Lanfranchi et al, 2017); it is an index of cardiac sympathetic (β-adrenergic) activity (Krohová et al, 2017). The SI is purely based on the RR intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is a limitation that no autonomic stress maneuver designed to elicit sympathetic activation or a measure of sympathetic variability was employed. PEP can be influenced by several cardiovascular confounders including left ventricular end-diastolic pressure, systemic vascular resistance and diastolic blood pressure (Krohova et al, 2017 ), and none of these factors were controlled for. The inclusion of QT-variability, an index of spontaneous beat-to-beat fluctuations in the QT-interval indexing cardiac repolarization lability (Baumert et al, 2016 ), would have strengthened the results.…”
Section: Discussionmentioning
confidence: 99%
“…The use of impedance cardiography for hemodynamic measurements may represent another study limitation; this method was shown to potentially over-or underestimate the results during NIV compared to the thermo-dilution method (14). Nevertheless, impedance cardiography is an established non-invasive method to assess hemodynamic functions in both experimental (15) and clinical (16) studies, which is reliable when assessing trends (17).…”
Section: Discussionmentioning
confidence: 99%